Anal cancer: French Intergroup Clinical Practice Guidelines for diagnosis, treatment and follow-up (SNFGE, FFCD, GERCOR, UNICANCER, SFCD, SFED, SFRO, SNFCP). Issue 8 (August 2017) - Moureau-Zabotto, Laurence; Vendrely, Veronique; Abramowitz, Laurent; Borg, Christophe; Francois, Eric; Goere, Diane; Huguet, Florence; Peiffert, Didier; Siproudhis, Laurent; Ducreux, Michel; Bouché, Olivier
Abstract: Introduction: This document is a summary of the French Intergroup guidelines regarding the management of anal carcinomas, published in November 2016. Methods: It is a collaborative work produced under the auspices of the majority of the French medical societies involved in the management of anal cancer. It is based on the previous guidelines published in 2010. Recommendations are graded in three categories, according to the amount of evidence found in the literature. Results: Non-metastatic anal carcinomas can be divided into two risk groups, according to magnetic resonance imaging (MRI) or endorectal-ultrasonograpy. Localized small cancers (T1N0) are mainly treated by exclusive radiation therapy in the case of cancers of the anal canal, or by surgery in the case of cancers of the anal margin. The recommended treatment of locally advanced tumours (T2-T4, N0-N2) is definitive concomitant radio-chemotherapy. Salvage surgery should be reserved for patients with poor response, tumour progression or local relapse after radio-chemotherapy, or in cases of persistent vaginal fistula or total anal incontinence after the cessation of radio-chemotherapy. In the case of metastatic tumours, current therapeutic recommendations are based on less robust evidence; with chemotherapy playing a major role. Conclusion: These recommendations are permanently being reviewed, and each individual case must be discussed inside a multidisciplinary team.